Clinical Legal Education in the Theory and Practice in the Indonesian Law School - Arifin, Saru (The Indonesian Journal of International Clinical Legal Education, 2019)
This short paper delves into the integration of Clinical Legal Education (CLE) in both theoretical understanding and practical application within Indonesian law schools. CLE serves as a bridge between legal theory and real-world practice, enriching legal education with tangible experiences. The theoretical dimension involves leveraging CLE to enhance students' comprehension of legal concepts, fostering a deeper understanding of the intricacies of the law. This theoretical grounding is complemented by the practical aspect, where students engage in hands-on experiences to develop essential legal skills such as research, client counseling, negotiation, and courtroom advocacy. In the Indonesian context, CLE is strategically positioned to address societal needs and promote social justice. Through real-world case engagements, students learn to navigate the complexities of the legal system while contributing to the resolution of legal issues that impact communities. This practical exposure not only reinforces theoretical knowledge but also instills a sense of social responsibility among future legal practitioners. The integration of CLE into the curriculum of Indonesian law schools brings forth a paradigm shift in legal education. Students not only gain a comprehensive understanding of legal principles but also acquire the practical skills and ethical considerations necessary for successful legal practice. This abstract emphasizes the holistic approach of CLE, positioning it as a transformative force that harmonizes theory and practice in the realm of legal education in Indonesia.